Impacts of elevated CO2 and partial defoliation on mineral element composition in rice - Gao, Bo; Hu, Shaowu; Zhou, Mingyuan; Jing, Liquan; Wang, Yunxia; Zhu, Jianguo; Sun, Xingxing; Wang, Kai; Wang, Yulong; Yang, Lianxin (Frontiers in Plant Science, 2024)
Introduction This study explores how elevated CO2 concentration may alter the source-sink dynamics in rice by providing additional carbon for photosynthesis, thereby affecting nutrient absorption and distribution. Methods A free-air CO2 enrichment experiment was conducted on a japonica cultivar Wuyunjing 27 in 2017 and 2018 growing seasons. The plants were exposed to ambient and elevated CO2 level (increased by 200 μmol·mol-1) and two source-sink manipulation treatments (control with no leaf cutting and cutting off the top three leaves at heading). Results The elevated CO2 significantly increased the above-ground biomass and the straw non-structural carbohydrate concentration by an average of 19.3% and 12.5%, respectively. Significant changes in the concentrations of N, S, Fe, and Zn in straw were noted under elevated CO2, with average decreases by 7.1, 7.2, 11.6, and 10.1%, respectively. The exposure to elevated CO2 significantly enhanced the elements accumulation, yet it had minimal impact on their distribution across different organs. When compared to intact rice, removing the top three leaves at heading reduced the above-ground biomass by 36.8% and the straw non-structural carbohydrate content by 44.8%. Leaf-cutting generally increased the concentration of elements in stem, leaf, and grain, likely due to a concentration effect from reduced biomass and carbohydrate accumulation. Leaf-cutting reduced element accumulation and shifted element allocation in rice organs. It increased the proportion of elements in stems while reduced their presence in leaves and grains. Discussion Our study suggests that a dilution effect may cause a decrease in mineral elements concentrations under elevated CO2 because of the increase in biomass and carbohydrates.